Parental Involvement and Its Relationship with High School Students' Learning Achievement: A Comparative Study of Urban and Rural Schools - Nurnisaa, Nurnisaa; Lestari, Mugi (International Journal of Ethno-Sciences and Education Research, 2025)
This study aims to analyze the relationship between parental involvement and academic achievement of high school students by comparing schools in urban and rural areas. A comparative quantitative approach with correlational survey method was employed, involving 100 eleventh-grade students (50 from urban schools and 50 from rural schools). Data were collected through questionnaires measuring parental involvement based on Epstein's theory and documentation of report card scores for academic achievement. Results revealed a significant positive correlation (r = 0.621; p < 0.05) between parental involvement and student academic achievement. Independent Samples T-Test showed a significant difference (p = 0.002) in academic achievement between urban school students (M = 86.20) and rural school students (M = 82.45). Similarly, parental involvement in urban schools demonstrated higher average scores (M = 82.14; SD = 6.43) compared to rural schools (M = 74.88; SD = 7.12). These findings confirm that geographical context influences patterns of parental involvement in education and its impact on academic achievement. This study contributes to educational policy formulation, particularly in developing effective parental involvement strategies tailored to specific school environments, and highlights the importance of collaborative programs between schools and families to address the urban-rural achievement gap.